2009
DOI: 10.1007/s00436-009-1627-2
|View full text |Cite
|
Sign up to set email alerts
|

Japanese monkey (Macaca fuscata) with alveolar echinococcosis after treatment with albendazole for 10 years: serodiagnosis and determination of albendazole metabolites

Abstract: In 1997, an outbreak of alveolar echinococcosis in Japanese monkeys (Macaca fuscata) occurred in a zoo in Hokkaido, Japan. Twelve infected monkeys from a colony (n = 57) were diagnosed serologically by Western blotting, and ultrasonography showed the presence of tumor-like tissue in the livers of nine monkeys. The 12 infected monkeys have been treated with albendazole for 10 years without surgical resection. Ten of these monkeys have died so far; diagnoses were confirmed histopathologically through autopsy. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
5
1
Order By: Relevance
“…Additional cases of hydatid disease have been seen in a thick-tailed galago (Otolemur crassicaudatus), a ringtailed lemur (Lemur catta), and rhesus macaques, one of which had a primary lung cyst with subsequent spread to the abdomen (Palotay and Uno, 1975). Several cases of "alveolar echinococcosis" due to E. multilocularis also have been reported in nonhuman primates, most of which had either primary or concurrent pulmonary involvement (Garcia et al, 2002;Yamano et al, 2009). Long-term albendazole was efficacious in treatment of some of the Japanese macaques in the outbreak described by Yamano et al (2009).…”
Section: Hydatidosismentioning
confidence: 99%
See 1 more Smart Citation
“…Additional cases of hydatid disease have been seen in a thick-tailed galago (Otolemur crassicaudatus), a ringtailed lemur (Lemur catta), and rhesus macaques, one of which had a primary lung cyst with subsequent spread to the abdomen (Palotay and Uno, 1975). Several cases of "alveolar echinococcosis" due to E. multilocularis also have been reported in nonhuman primates, most of which had either primary or concurrent pulmonary involvement (Garcia et al, 2002;Yamano et al, 2009). Long-term albendazole was efficacious in treatment of some of the Japanese macaques in the outbreak described by Yamano et al (2009).…”
Section: Hydatidosismentioning
confidence: 99%
“…Several cases of "alveolar echinococcosis" due to E. multilocularis also have been reported in nonhuman primates, most of which had either primary or concurrent pulmonary involvement (Garcia et al, 2002;Yamano et al, 2009). Long-term albendazole was efficacious in treatment of some of the Japanese macaques in the outbreak described by Yamano et al (2009). A detailed account of imaging studies performed on two of these macaques was described by Kishimoto et al (2009), which demonstrated mineralization of many of the lesions.…”
Section: Hydatidosismentioning
confidence: 99%
“…This, however, was not validated, but would make sense if the pharmacokinetics is similar to what was described for sheep [14]. For Japanese monkeys, no ABZSO 2 but significant plasma levels of ABZSO and ABZSO 2 ‐NH 2 were reported [32]. This finding is difficult to comprehend because ABZSO 2 ‐NH 2 is a metabolite of ABZSO 2 (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…A similar HPLC pattern was monitored in sera of Japanese monkeys ( Macaca fuscata ) with alveolar echinococcosis that were treated with ABZ. In this work, the two ABZ metabolite peaks were assigned to ABZSO and ABZSO 2 ‐NH 2 [32]. No scientific article about the metabolism of ABZ in gorillas was found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the antibody response time course in the postoperative stage offers information about curative effects (Fujimoto et al , 2005). In non-human primates such as the Japanese monkey ( Macaca fuscata ), we previously diagnosed AE by serodiagnosis and ultrasonography (Sato et al , 2005) and showed it to be almost cured after treatment with albendazole for 10 years, by imaging analysis and the disappearance of the 18 kDa band in a WB test (Kishimoto et al , 2009; Yamano et al , 2009c).…”
Section: Discussionmentioning
confidence: 99%